A simple turn-on fluorescent chemosensor for CO2 based on aggregation-induced emission: Application as a CO2 absorbent screening method. (March 2019) - Jang, Mincheol; Kang, Seungyoon; Han, Min Su
Abstract: An α-cyanostilbene-based fluorescent chemosensor, which includes a primary amine, was developed for the quantitative analysis of CO2 in solution. (Z)-3-(4-(3-Aminopropoxy)phenyl)-2-(4-nitrophenyl)acrylonitrile (1 ) reacts with CO2 and enables a turn-on type CO2 chemosensor with increased fluorescence due to aggregation-induced emission. More importantly, 1 required no additives such as an amine media for detecting CO2, and the limit of detection was estimated to be ∼26 ppm. This system was successfully applied to determine the relative efficiency of CO2 absorbents dependent on the fluorescence change in1 . The use of this chemosensor as a CO2 absorbent screening method suggests that1 may be used to develop a high-throughput screening method for the evaluation of high-performance CO2 absorbents. Graphical abstract: Highlights: α-Cyanostilbene-based fluorescent chemosensor for CO2 was developed by using AIE. Chemosensor enables the detection of CO2 with no additives, such as amine and anion. This chemosensor was applied to determine the relative efficiency of CO2 absorbents.